Method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate

Through the two-step leaching process and hydrothermal reaction, the problems of low metal recovery rate, high energy consumption and serious pollution in the recycling process of waste lithium iron phosphate batteries in the prior art are solved, and efficient separation and preparation of high-purity iron phosphate are achieved. The process is green and environmentally friendly and suitable for large-scale applications.

CN119841293AInactive Publication Date: 2025-04-18CHIZHOU CN NEW MATERIALS & TECHNOLOGY CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510345669.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing waste lithium iron phosphate battery recycling technology has problems such as low metal recovery rate, high energy consumption, long process and serious metal entrainment losses. The traditional acid-implanting process has strong acid corrosion, high treatment cost and is prone to secondary pollution.

Method used

The two-step leaching process is adopted to adjust the pH and temperature step by step of the primary and secondary leaching liquids, and the complexation and antioxidant properties of components such as citric acid, ascorbic acid, ammonium persulfate and ethylenediaminetetraacetic acid are used to achieve efficient separation of lithium iron. Then, the amorphous FePO4•2H2O is converted into high crystallinity iron phosphate through hydrothermal reaction and carbon source template effect.

Benefits of technology

It realizes efficient separation of lithium iron and the preparation of high-purity iron phosphate. The overall process is green and environmentally friendly, has low energy consumption, is suitable for large-scale applications, and reduces pollution from the source, which is in line with the concept of green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841293A_ABST
    Figure CN119841293A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste battery material recycling and reusing, and particularly discloses a method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate. Comprising the following steps: disassembling a battery and processing to obtain positive electrode powder; carrying out ultrasonic leaching on lithium by adopting a citric acid-ascorbic acid-ammonium persulfate-ethylenediamine tetraacetic acid system, and separating lithium-containing liquid from residues; carrying out deep leaching on the residues through an oxalic acid-ammonium persulfate-thiourea-ammonium fluoride system to obtain iron, adjusting the pH value, and then carrying out flocculation to obtain amorphous FePO42H2O; and carrying out hydrothermal reaction on the precursor, phosphoric acid and a carbon source, and calcining to obtain the battery-grade iron phosphate. Compared with the problems that in the prior art, a leachate system is high in equipment corrosivity, large in treatment difficulty of acid wastewater containing heavy metal, poor in lithium-iron separation purity, low in efficiency and the like, efficient lithium-iron separation is achieved through two-step leaching, high-purity iron phosphate is directly synthesized, and the whole process is environmentally friendly, low in energy consumption and suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of recycling and reusing waste battery materials, and more specifically, to a method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate. Background Art

[0002] In today's era of equal emphasis on energy and environmental protection, lithium iron phosphate batteries have become one of the mainstream positive electrode materials for power batteries due to their low raw material cost, low toxicity and high thermal stability. However, with an average service life of 5-8 years and the continued increase in market holdings, the recycling of waste lithium iron phosphate batteries needs to be urgently addressed. Leakage of organic matter such as plastic shells and electrolytes will pollute the atmosphere, soil and domestic water; metallic lithium reacts with water to generate hydrogen, which is prone to explosion, and metals enter the human body through ecological cycles, seriously threatening physical and mental health. Recycling such batteries can not only reduce environmental pollution and alleviate resource depletion, but is also a key technical path to achieve efficient recycling of resources, reduce environmental pollution risks, and improve the economic benefits of the industry.

[0003] At present, the recycling technology of waste lithium iron phosphate batteries is mainly divided into physical method, chemical method and biological method. The physical method separates metal and non-metal components by crushing and screening, but there are problems such as low metal recovery rate and high energy consumption. The chemical method is mainly based on hydrometallurgy, dissolving the positive electrode material by acid leaching, and then preparing iron phosphate by precipitation and calcination. However, in the traditional acid leaching process, lithium and iron are leached simultaneously, and separation requires multi-step precipitation or ion exchange. The process is lengthy and the metal entrainment loss is serious. The strong acid system is highly corrosive, and the waste liquid contains high concentrations of Cl - and SO 2- , the processing cost is high and it is easy to cause secondary pollution. In view of the above problems, although the existing technology has tried to improve, it still has limitations. For example, patent CN117602604A proposes a reduction acid leaching combined with impurity removal process, but it is necessary to introduce iron powder and nitric acid, resulting in the risk of impurity residues; patent CN117658088A uses ionic liquid ball milling activation, although it improves the lithium leaching rate, but the process is complicated and the cost is high. Therefore, the present invention provides a method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate to solve the above-mentioned technical problems. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate. The efficient separation of lithium and iron is achieved through two-step leaching, and high-purity iron phosphate is directly synthesized. The overall process is green and environmentally friendly, with low energy consumption, and is suitable for large-scale application.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, dispersing lithium iron phosphate battery powder in a primary leachate, adjusting the pH to 1.5-3.0, and ultrasonically treating at 35-45° C. for 1-3 h, then filtering to obtain a leachate and a primary residue; S3, transfer the primary residue to the secondary leachate, adjust the pH to 1.0-1.5, continue stirring at 60-80°C for 2-4 hours, filter to obtain an acidic leachate, then drop ammonia water to the leachate until the pH is 2.5-3.0, add polyacrylamide, age at 50-70°C for 0.5-2 hours, and centrifuge to obtain amorphous FePO4•2H2O; S4. Disperse amorphous FePO4•2H2O in phosphoric acid solution, add carbon source, and perform hydrothermal reaction at 160-180°C for 10-13h to obtain filter residue. Dry, calcine, crush and sieve the filter residue to obtain battery-grade iron phosphate.

[0006] Preferably, the primary leaching solution in step S2 is composed of 1-2 mol / L citric acid, 0.1-0.5 mol / L ascorbic acid, 0.05-0.1 mol / L ammonium persulfate and 0.03-0.05 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.2-0.5:0.06-0.1:0.02-0.05.

[0007] Preferably, in step S2, the mass ratio of the lithium iron phosphate battery powder to the primary leaching solution is 1:8-12.

[0008] Preferably, the secondary leaching solution in step S3 is composed of 1-1.5 mol / L oxalic acid, 0.08-0.2 mol / L ammonium persulfate, 0.01-0.03 mol / L thiourea and 0.01-0.03 mol / L ammonium fluoride in a molar ratio of 1:0.1-0.3:0.05-0.08:0.05-0.08.

[0009] Preferably, in step S3, the mass ratio of the primary residue, the secondary leaching solution and the polyacrylamide is 1-3:8-12:0.5-0.8.

[0010] Preferably, in step S4, the mass ratio of amorphous FePO4•2H2O to phosphoric acid solution is 1:12-15.

[0011] Preferably, the mass fraction of the phosphoric acid solution in step S4 is 2-5%.

[0012] Preferably, the carbon source in step S4 is at least one of glucose, sucrose and polyethylene glycol, and the added amount is 3-5% of the mass of amorphous FePO4•2H2O.

[0013] Preferably, in step S4, the calcination temperature is 450-550° C., and the calcination time is 2-4 hours.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts a two-step leaching process. The primary leachate is compounded with citric acid, ascorbic acid, ammonium persulfate and ethylenediaminetetraacetic acid. The complexation and antioxidant properties of each component are utilized to initially and efficiently leach most of the soluble metal elements with high selectivity. The secondary leachate is composed of oxalic acid, ammonium persulfate, thiourea and ammonium fluoride in a specific proportion, which deeply leach the metal elements in the primary residue and realize the control of the leaching order and degree of different metal elements, which not only improves the overall recovery rate and purity of the metal elements, but also facilitates the separation of impurities. The hydrothermal conditions are combined with the carbon source template effect to convert amorphous FePO4•2H2O into high-crystallinity iron phosphate, which can control the size and morphology of the iron phosphate particles and form a stable crystal structure, which is beneficial to the charge and discharge kinetics of the positive electrode material of lithium-ion batteries. The method abandons highly corrosive and highly toxic leaching agents throughout the process, adopts a mild leaching solution system, reduces pollution from the source, and conforms to the concept of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Unless otherwise specified, the raw materials used in the present invention are all conventional products purchased from the market.

[0019] Among them, polyacrylamide: purchased from Aladdin, CAS9003-05-8, item number P434411; Polyethylene glycol: purchased from Aladdin, CAS25322-68-3, item number P615477.

[0020] Example 1

[0021] A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:8 g / mL, adjusting the pH to 1.5, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 50 KHz and 35° C. for 3 h, wherein the primary leachate is composed of 1.0 mol / L citric acid, 0.1 mol / L ascorbic acid, 0.05 mol / L ammonium persulfate and 0.03 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.2:0.06:0.02; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.0, controlling the stirring rate to 200 rpm, stirring continuously at 60°C for 4 hours, filtering to obtain an acidic leachate, then dripping ammonia water thereto until the pH value reaches 2.5, adding polyacrylamide, aging at 50°C for 2 hours, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.0 mol / L oxalic acid, 0.08 mol / L ammonium persulfate, 0.01 mol / L thiourea and 0.01 mol / L ammonium fluoride in a molar ratio of 1:0.1:0.05:0.05; S4. Mix amorphous FePO4•2H2O and 2% by mass phosphoric acid solution in a solid-liquid ratio of 1:12, add polyethylene glycol, and perform hydrothermal reaction at 160°C for 13 hours to obtain a filter residue. Dry the filter residue, calcine it at 450°C for 4 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0022] Example 2

[0023] A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:9 g / mL, adjusting the pH to 1.8, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 54 kHz and 38° C. for 2.8 h, wherein the primary leachate is composed of 1.2 mol / L citric acid, 0.2 mol / L ascorbic acid, 0.06 mol / L ammonium persulfate and 0.04 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.3:0.08:0.03; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.2, controlling the stirring rate to 220 rpm, stirring continuously at 62°C for 3.8 hours, filtering to obtain an acidic leachate, then dripping ammonia water therein to pH 2.6, adding polyacrylamide, aging at 52°C for 1.8 hours, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.1 mol / L oxalic acid, 0.1 mol / L ammonium persulfate, 0.015 mol / L thiourea and 0.013 mol / L ammonium fluoride in a molar ratio of 1:0.2:0.06:0.05; S4. Mix amorphous FePO4•2H2O and 3% by mass phosphoric acid solution in a solid-liquid ratio of 1:13, add sucrose, and perform hydrothermal reaction at 163°C for 12 hours to obtain a filter residue. Dry the filter residue, calcine it at 460°C for 3.8 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0024] Example 3

[0025] A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:10 g / mL, adjusting the pH to 2.0, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 55 KHz and 40° C. for 2.5 h, wherein the primary leachate is composed of 1.3 mol / L citric acid, 0.3 mol / L ascorbic acid, 0.08 mol / L ammonium persulfate and 0.04 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.4:0.08:0.04; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.2, stirring continuously at 65°C for 3.7 hours, filtering to obtain an acidic leachate, then dripping ammonia water thereinto until the pH value reaches 2.8, adding polyacrylamide, aging at 56°C for 1.8 hours, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.4 mol / L oxalic acid, 0.13 mol / L ammonium persulfate, 0.018 mol / L thiourea and 0.02 mol / L ammonium fluoride in a molar ratio of 1:0.2:0.07:0.08; S4. Mix amorphous FePO4•2H2O and 4% by mass phosphoric acid solution in a solid-liquid ratio of 1:14, add glucose, and perform hydrothermal reaction at 170°C for 11 hours to obtain a filter residue. Dry the filter residue, calcine it at 490°C for 3.6 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0026] Example 4

[0027] A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:12 g / mL, adjusting the pH to 2.8, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 65 KHz and 45° C. for 1.5 h, wherein the primary leachate is composed of 1.8 mol / L citric acid, 0.5 mol / L ascorbic acid, 0.1 mol / L ammonium persulfate and 0.04 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.5:0.1:0.05; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.4, stirring continuously at 80°C for 2.2 hours, filtering to obtain an acidic leachate, then dripping ammonia water therein to a pH of 2.8, adding polyacrylamide, controlling the stirring rate to 350 rpm, aging at 70°C for 1 hour, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.4 mol / L oxalic acid, 0.18 mol / L ammonium persulfate, 0.03 mol / L thiourea and 0.025 mol / L ammonium fluoride in a molar ratio of 1:0.3:0.08:0.06; S4. Mix amorphous FePO4•2H2O and 5% by mass phosphoric acid solution in a solid-liquid ratio of 1:15, add glucose, and perform hydrothermal reaction at 170°C for 10.2 hours to obtain a filter residue. Dry the filter residue, calcine it at 550°C for 2 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0028] Example 5

[0029] A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:12 g / mL, adjusting the pH to 3.0, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 65 KHz and 45° C. for 1 h, wherein the primary leachate is composed of 2 mol / L citric acid, 0.5 mol / L ascorbic acid, 0.1 mol / L ammonium persulfate and 0.05 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.5:0.1:0.05; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.5, stirring continuously at 80°C for 2 hours, filtering to obtain an acidic leachate, then dripping ammonia water thereto until the pH reaches 3.0, adding polyacrylamide, aging at 70°C for 0.5 hours, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.5 mol / L oxalic acid, 0.2 mol / L ammonium persulfate, 0.03 mol / L thiourea and 0.03 mol / L ammonium fluoride in a molar ratio of 1:0.3:0.08:0.08; S4. Mix amorphous FePO4•2H2O and 5% by mass phosphoric acid solution in a solid-liquid ratio of 1:15, add glucose, and perform hydrothermal reaction at 180°C for 10 hours to obtain a filter residue. Dry the filter residue, calcine it at 550°C for 2 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0030] Comparative Example 1 A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to the primary leachate at a solid-liquid ratio of 1:12 g / mL, adjusting the pH to 2.8, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 65 KHz and 45° C. for 1.5 h, wherein the primary leachate is composed of 1.8 mol / L hydrochloric acid, 0.1 mol / L ammonium persulfate and 0.04 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.1:0.05; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.4, stirring continuously at 80°C for 2.2 hours, filtering to obtain an acidic leachate, then dripping ammonia water therein to a pH of 2.8, adding polyacrylamide, controlling the stirring rate to 350 rpm, aging at 70°C for 1 hour, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.4 mol / L hydrochloric acid, 0.18 mol / L ammonium persulfate, 0.03 mol / L thiourea and 0.025 mol / L ammonium fluoride in a molar ratio of 1:0.3:0.08:0.06; S4. Mix amorphous FePO4•2H2O and 5% by mass phosphoric acid solution in a solid-liquid ratio of 1:15, add glucose, and perform hydrothermal reaction at 170°C for 10.2 hours to obtain a filter residue. Dry the filter residue, calcine it at 550°C for 2 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0031] Comparative Example 2 A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:12 g / mL, adjusting the pH to 2.8, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 65 KHz and 45° C. for 1.5 h, wherein the primary leachate is composed of 1.8 mol / L citric acid, 0.5 mol / L ascorbic acid and 0.1 mol / L ammonium persulfate in a molar ratio of 1:0.5:0.1; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.4, stirring continuously at 80°C for 2.2 hours, filtering to obtain an acidic leachate, then dripping ammonia water therein to a pH of 2.8, adding polyacrylamide, controlling the stirring rate to 350 rpm, aging at 70°C for 1 hour, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.4 mol / L oxalic acid, 0.18 mol / L ammonium persulfate, 0.03 mol / L thiourea and 0.025 mol / L ammonium fluoride in a molar ratio of 1:0.3:0.08:0.06; S4. Mix amorphous FePO4•2H2O and 5% by mass phosphoric acid solution in a solid-liquid ratio of 1:15, add glucose, and perform hydrothermal reaction at 170°C for 10.2 hours to obtain a filter residue. Dry the filter residue, calcine it at 550°C for 2 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0032] Comparative Example 3 A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:12 g / mL, adjusting the pH to 2.8, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 65 KHz and 45° C. for 1.5 h, wherein the primary leachate is composed of 1.8 mol / L citric acid, 0.5 mol / L ascorbic acid, 0.1 mol / L ammonium persulfate and 0.04 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.5:0.1:0.05; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.4, stirring continuously at 80°C for 2.2 hours, filtering to obtain an acidic leachate, then dripping ammonia water to pH 2.8, adding polyacrylamide, controlling the stirring rate to 350 rpm, aging at 70°C for 1 hour, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.4 mol / L oxalic acid and 0.18 mol / L ammonium persulfate in a molar ratio of 1:0.3; S4. Mix amorphous FePO4•2H2O and 5% by mass phosphoric acid solution in a solid-liquid ratio of 1:15, add glucose, and perform hydrothermal reaction at 170°C for 10.2 hours to obtain a filter residue. Dry the filter residue, calcine it at 550°C for 2 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0033] Comparative Example 4 A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate comprises the following steps: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, adding lithium iron phosphate battery powder to a primary leachate at a solid-liquid ratio of 1:12 g / mL, adjusting the pH to 2.8, and filtering to obtain a leachate and a primary residue after ultrasonic treatment at 65 KHz and 45° C. for 1.5 h, wherein the primary leachate is composed of 1.8 mol / L citric acid, 0.5 mol / L ascorbic acid, 0.1 mol / L ammonium persulfate and 0.04 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.5:0.1:0.05; S3, transferring the primary residue to the secondary leachate, adjusting the pH to 1.4, stirring continuously at 80°C for 2.2 hours, filtering to obtain an acidic leachate, then dripping ammonia water therein to a pH of 2.8, adding polyacrylamide, controlling the stirring rate to 350 rpm, aging at 70°C for 1 hour, and centrifuging to obtain amorphous FePO4•2H2O, wherein the secondary leachate is composed of 1.4 mol / L oxalic acid, 0.18 mol / L ammonium persulfate, 0.03 mol / L thiourea and 0.025 mol / L ammonium fluoride in a molar ratio of 1:0.3:0.08:0.06; S4. Mix amorphous FePO4•2H2O and 5% by mass phosphoric acid solution in a solid-liquid ratio of 1:15, add activated carbon, and perform hydrothermal reaction at 170°C for 10.2 hours to obtain a filter residue. Dry the filter residue, calcine it at 550°C for 2 hours, and crush and sieve it to obtain battery-grade iron phosphate.

[0034] Test method: The lithium leaching rate and iron leaching rate of the leaching solutions in Examples 1-5 and Comparative Examples 1-4 were calculated, and the purity of the final battery-grade iron phosphate was tested. The test results are shown in Table 1.

[0035] Table 1 Test items Lithium leaching rate / % Iron leaching rate Product purity Product Description Example 1 93.07 97.17 97.46 Uniform particles and good dispersion Example 2 93.94 97.59 98.01 Uniform particles and good dispersion Example 3 94.41 98.41 98.74 Uniform particles and good dispersion Example 4 95.28 99.03 99.57 Uniform particles and good dispersion Example 5 95.01 98.64 99.13 Uniform particles and good dispersion Comparative Example 1 75.53 85.74 96.44 Particles are agglomerated and irregular in shape Comparative Example 2 82.54 82.16 97.26 Poor particle dispersion Comparative Example 3 77.19 78.36 95.22 The particles are porous and complex in shape Comparative Example 4 92.88 97.21 91.23 Particle agglomeration The embodiment adopts a citric acid-ascorbic acid-ammonium persulfate-ethylenediaminetetraacetic acid (EDTA) compound system. Citric acid, as a weak acid and chelating agent, gently dissolves metals; the reducing property of ascorbic acid inhibits metal oxidation and reduces side reactions; ammonium persulfate promotes metal dissolution through oxidation; EDTA selectively complexes metal ions to enhance the lithium-iron separation efficiency. However, Comparative Example 1 uses highly corrosive hydrochloric acid, which leads to equipment loss and impurity introduction, and lacks selective complexing ability, resulting in low lithium leaching rate and iron entrainment loss. Comparative Example 2 lacks EDTA, the complexing ability decreases, the lithium-iron separation efficiency decreases, and the iron leaching rate decreases significantly.

[0036] In the embodiment, the pH and the leaching agent (oxalic acid-ammonium persulfate-thiourea-ammonium fluoride) are controlled step by step, thiourea reduces the high-valent iron to promote dissolution, and ammonium fluoride forms a soluble complex with iron, deeply leaching the residual iron and reducing the residual impurities. The secondary leaching solution of Comparative Example 3 lacks thiourea and ammonium fluoride, resulting in incomplete leaching of iron and reduced product purity.

[0037] In the example, the carbon sources such as glucose and sucrose provide templates in the hydrothermal reaction, regulate the growth of iron phosphate crystal nuclei, and form uniformly dispersed particles. However, in comparative example 4, activated carbon is used, and its surface inertness cannot effectively guide crystallization, resulting in particle agglomeration and irregular morphology.

[0038] In summary, the embodiment achieves efficient separation of lithium iron and controllable preparation of high-purity iron phosphate through the synergistic effect of a mild and efficient leaching system, step-by-step selective leaching and carbon source template effect, while the comparative example has significantly reduced process efficiency due to missing components or improper reagent selection.

[0039] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing battery-grade iron phosphate by recycling waste lithium iron phosphate, characterized in that: The following steps are involved: S1. Discharging and disassembling waste lithium iron phosphate batteries to obtain positive electrode sheets, and then peeling, crushing and screening to obtain lithium iron phosphate battery powder; S2, dispersing lithium iron phosphate battery powder in a primary leachate, adjusting the pH to 1.5-3.0, and ultrasonically treating at 35-45° C. for 1-3 h, then filtering to obtain a leachate and a primary residue; S3, transfer the primary residue to the secondary leachate, adjust the pH to 1.0-1.5, continue stirring at 60-80°C for 2-4 hours, filter to obtain an acidic leachate, then drop ammonia water to the leachate until the pH is 2.5-3.0, add polyacrylamide, age at 50-70°C for 0.5-2 hours, and centrifuge to obtain amorphous FePO4•2H2O; S4. Disperse amorphous FePO4•2H2O in phosphoric acid solution, add carbon source, and perform hydrothermal reaction at 160-180°C for 10-13h to obtain filter residue. Dry, calcine, crush and sieve the filter residue to obtain battery-grade iron phosphate.

2. The method according to claim 1, characterized in that In step S2, the primary leaching solution is composed of 1-2 mol / L citric acid, 0.1-0.5 mol / L ascorbic acid, 0.05-0.1 mol / L ammonium persulfate and 0.03-0.05 mol / L ethylenediaminetetraacetic acid in a molar ratio of 1:0.2-0.5:0.06-0.1:0.02-0.

05.

3. The method according to claim 1, characterized in that In the step S2, the mass ratio of the lithium iron phosphate battery powder to the primary leaching solution is 1:8-12.

4. The method according to claim 1, characterized in that The secondary leaching solution in step S3 is composed of 1-1.5 mol / L oxalic acid, 0.08-0.2 mol / L ammonium persulfate, 0.01-0.03 mol / L thiourea and 0.01-0.03 mol / L ammonium fluoride in a molar ratio of 1:0.1-0.3:0.05-0.08:0.05-0.

08.

5. The method according to claim 1, characterized in that In step S3, the mass ratio of the primary residue, the secondary leaching solution and the polyacrylamide is 1-3:8-12:0.5-0.

8.

6. The method according to claim 1, characterized in that In the step S4, the mass ratio of amorphous FePO4•2H2O to phosphoric acid solution is 1:12-15.

7. The method according to claim 1, characterized in that The mass fraction of the phosphoric acid solution in step S4 is 2-5%.

8. The method according to claim 1, characterized in that In step S4, the carbon source is at least one of glucose, sucrose and polyethylene glycol, and the added amount is 3-5% of the mass of the amorphous FePO4•2H2O.

9. The method according to claim 1, characterized in that: In step S4, the calcination temperature is 450-550° C., and the calcination time is 2-4 hours.

Citation Information

Patent Citations

  • Method for recycling and regenerating waste lithium iron phosphate battery positive electrode material

    CN113501510A

  • Method for removing aluminum from waste lithium iron phosphate battery powder and preparing battery-grade iron phosphate

    CN115838160A

  • Method for preparing battery-grade iron phosphate by utilizing positive electrode powder of waste lithium iron phosphate battery

    CN116177510A

  • Hydrated basic iron phosphate and preparation method thereof, and lithium iron phosphate positive electrode material and preparation method thereof

    CN118771332A

  • Method for regenerating battery-grade iron phosphate from phosphorus iron slag after lithium extraction

    CN119218951A